PENERAPAN METODE AWARENESS DALAM MENINGKATKAN MINAT BACA MASYARAKAT UNTUK MENDUKUNG LAYANAN PROGRAM TAMAN BACAAN MASYARAKAT (TBM) - Ahmad Syahid; Ika Rizqi Meilya (P2M STKIP Siliwangi, 2022)
The focus of this research problem is related to the reading interest of the community around Taman Baca Masyarakat Cahaya Karawang Regency. There are two factors that can affect reading interest, including internal factors and external factors. Internal factors include people who tend to be lazy to read, then busy activities, while external factors include the lack of adequate facilities or infrastructure, then the influence of the environment and the tendency of people to be more interested in multimedia. The purpose of the research includes to obtain an overview of the empirical condition of reading interest, knowing the steps of implementing awareness methods, as well as the advantages and disadvantages of applying awareness methods. Qualitative approaches with descriptive methods are applied in this study. Data collection techniques applied in research include interviews, observations, library studies, and documentation studies. The expected results, 1) Obtaining data on the empirical condition of people's reading interest, 2) Obtaining accurate data on the overview of measures to implement awareness methods to increase people's reading interest, 3) Obtaining data on the advantages and disadvantages of implementing awareness methods.